DEVELOPMENT OF THE TECHNIQUE OF OPERATION OF GEOTHERMAL SYSTEMS WHEN EXTRACTING ASSOCIATED GASES - G. Ya. Akhmedov; A. S. Kurbanismailova (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives. The aim of the study is to develop a method of operating geothermal energy systems in the mode without scaling when disposing of flammable gases with geothermal water in wells with a low gas factor.Method. The studies were conducted on the basis of analyzing the content of associated flammable gases in the underground thermal mineral waters of the North Caucasus and Ciscaucasian deposits and assessing the possibility of their utilization and use for heating and hot water supply. In this case, the laws of dissolution and desorption of methane and carbon dioxide from groundwater solutions with the content of scale-forming components, in particular, calcium carbonate, are used.Result. On the basis of the conducted research, it was found that the operation of g eothermal systems in the power industry should be carried out after preliminary withdrawal of the maximum possible amount of associated flammable gases from a water solution, while maintaining the content of carbon dioxide in water at a level above the equilibrium value. The scheme of the effective operation of thermal distribution stations with the prevention of carbonate deposits in them is given by using the products of associated gas combustion in the waste water when it is pumped back into the aquifer.Conclusion. As a result of the research conducted, a method of operating geothermal energy systems in a non-salt-scale mode has been developed for utilization of combustible gases associated with geothermal water. It has been established that in order to accelerate the dissolution of carbon dioxide in water to stabilize it before entering heat-exchange equipment, it is advisable to increase the partial pressure of carbon dioxide to values exceeding by an order of magnitude the equilibrium at a given temperature. At the same time, before pumping waste water back into the aquifer, excess carbon dioxide is removed from the water.